Barakatology from a Religious Respective in Social Life - Hidayat, Ibrahim Nur (Journal Corner of Education, Linguistics, and Literature, 2025)
Barakatology, or the study of blessings (barakah), is a fundamental aspect of religious life that requires a deep understanding of its concept, implementation, and implications in religious practice. This research examines the theological, spiritual, and practical dimensions of barakatology in the context of modern religious life through a comprehensive descriptive-analytical approach. The study reveals that barakatology plays a multidimensional role in religious life, not only as an abstract theological concept but also as a practical guide that can be implemented in everyday life. The analysis shows that understanding blessings can enrich an individual's spiritual dimension and provide deeper meaning to religion, creating a more intimate relationship between worshippers and the Creator. The research findings indicate that barakatology serves as a bridge connecting the vertical (relationship with God) and horizontal (relationships with others) aspects of religious life. Implementing the principles of barakatology has been proven to improve the quality of spiritual and social life for religious communities, provide inner peace, and strengthen moral values within society. This study concludes that barakatology is a discipline with high relevance in the context of contemporary religious life, offering spiritual solutions to modern challenges and providing a solid framework for the development of a holistic and sustainable spirituality.